Integrasi manajemen strategi dan teknologi finansial untuk meningkatkan efektivitas operasional bank syariah - Asy'ari, Hilda Aulia (Maliki Interdisciplinary Journal, 2025)
The integration of strategic management and financial technology (fintech) is the key to optimizing the operational effectiveness of Islamic banks in the digital era. In the context of Islamic economics based on justice and transparency, the proper implementation of digital strategies strengthens the competitiveness of Islamic financial institutions while maintaining compliance with sharia values. This study aims to analyze in depth how the synergy between strategic planning and the adoption of financial technology can enhance efficiency, service quality, and product innovation in Islamic banks. A qualitative literature-based approach was used, drawing from recent national and international journals on digital transformation, strategic management, and Islamic finance. The integration of strategic management and financial technology improves operational effectiveness through business process optimization, increased transaction transparency, financing efficiency, and stronger financial inclusion. However, the success of this integration depends greatly on human resource readiness, adaptive regulatory support, and digital infrastructure strengthening aligned with maqashid sharia. Thus, collaboration between corporate strategy, digital innovation, and sharia governance becomes the foundation for strengthening the competitiveness of the Islamic banking industry in the era of the Industrial Revolution 5.0.